"Common rail twin cylinder diesel engine performance and emission running on Vegetable oils blended with Ethanol". (2018) - Yerrennagoudaru, Hiregoudar; Manjunatha, K.; Lakshmeekantha,; Venkatesh, K.
Abstract: In view of increasing pressure on crude oil reserves and environmental degradation as an outcome, fuels like Biofuel may present a sustainable solution as it can be produced from a wide range of carbon based feedstock. The present investigation evaluates Mahua oil, Rape seed oil, Mange seed oil 'blended with Ethanol as a fuel in C I engine. A Twin cylinder C I engine was adapted to study the brake thermal efficiency, brake specific energy consumption, and emissions with the fuel of Mahua oil, Rape seed oil, Mange seed oilblended with Ethanol. In this study, the diesel engine was tested usingMahua oil, Rape seed oil, Mange seed oilblended with Ethanol. Twin cylinder C I engine is able to run with Bio fuel but the engine needs to run by using diesel fuel first, then followed by Bio fuel and finished with diesel fuel as the last fuel usage before the engine turned off. The performance of the engine using Mahua oil, Rape seed oil, Mange seed oilblended with Ethanol compared to the performance of engine with diesel fuel. Experimental results of Mahua oil, Rape seed oil, Mange seed oilblended with Ethanol and Diesel fuel are also compared.